A new method for determination of the reliability index of distributed parameter systems - Pho, Nguyen Van (Vietnam Journal of Mechanics, 2003)
In this paper, a method to determine the reliability - index of distributed systems is proposed. By the new method, instead of finding jointly probability depending on multi - conditions of inequalities one can find probability depending on only one inequality and no requiring to know jointly density function of basic variables. Therefore, it is very favourable for the calculation of the reliability - index of mechanical systems with distributed parameter. For illustrating the proposed method, a simple example is considered